Use of Multielectrode Arrays and Statistical Analysis to Investigate the Pitting Probability of Copper. Part I: The Effect of Chloride. Issue 6 (1st June 2022) - Matin, Sina; Tahmasebi, Arezoo; Momeni, Mojtaba; Behazin, Mehran; Davison, Matt; Shoesmith, David W.; Noël, James J.
Abstract : Under some conditions, copper and copper alloys are either immune from corrosion or undergo slow uniform corrosion, generally considered a favourable situation, since predicting the damage incurred by the metal during a period of uniform corrosion is relatively straightforward. However, under conditions leading to surface passivation of Cu, localized corrosion might occur in the presence of aggressive oxidants. Therefore, the susceptibility of Cu to localized corrosion must be considered carefully to avoid unpredictable failures in Cu-based structures. Understanding the pitting probability of Cu is important for various applications, including the use of Cu-coated containers for the permanent disposal of used nuclear fuel. In this study, the pitting probability of Cu in chloride-containing solutions crudely representing the groundwater that might be found in a deep geologic repository (DGR) was investigated using electrochemical techniques and statistical analysis. The probabilities of both pitting and repassivation of Cu were found to increase with increasing [Cl − ]. The surface morphologies of copper electrodes in the same solution were also evaluated using scanning electron microscopy (SEM). The passive film on the surface of the copper electrode with the highest breakdown potential (Eb ) was found to be more protective than that on the electrode with the lowest Eb .